A mark of grace [large type] - Woodhouse, Kimberley, 1973- (Woodhouse, Kimberley, 1973- Secrets of the canyon, 2023)
"Ruth Anniston survived an injury that left her physically scarred, broken, and angry at God. Now she finds herself working behind the scenes as a kitchen supervisor at the El Tovar Hotel, hidden away from curious eyes. When money begins to disappear from the hotel, Ruth's entire livelihood is put at risk. Frank Henderson has at last succeeded in obtaining his dream job as the head chef at the El Tovar. But with the continuing thefts at the hotel, and his growing affection for Ruth, Frank's career--and his heart--are in jeopardy. As tensions run high, Ruth and Frank must work together to save the El Tovar and forge a new path for the future together. Bestselling author Kimberley Woodhouse invites you to experience the strength and beauty of friendship, family, and love in this grand historical tale"--